A Hybrid Ensemble and Blended Clustering Framework for Business Intelligent Academic Feedback Systems - Hemant Sharma,Dr. Hiren Joshi (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Recent advancements in machine learning and artificial intelligence haveenabled educational systems to provide more personalized learning experiences, moving beyond conventional approaches.